Contextualizing Nasr's Sufism In Education In The Modern Era - Basith, Yudril; Saiful Bahri; Dede Setiawan (Jurnal Pendidikan Islam Indonesia, 2024)
This article examines Seyyed Hossein Nasr's thoughts on contextualizing Sufism in education in the modern era. Nasr views Sufism as the key to reviving traditional Islamic values that have long been forgotten. Nasr calls for the importance of education, which develops intellectually and cultivates the human soul and personality. This article uses a qualitative approach with a type of literature study, examining Nasr's works and related literature to explore his thoughts on Sufism and education. The data collection technique used is documentation study; primary sources are obtained from Nasr's works, such as books, journal articles, and his writings that discuss Sufism, education, and his thoughts on these topics. Secondary data sources come from other literature relevant to this research. Data analysis was conducted using content analysis and hermeneutic analysis methods. The results show that contextualizing Sufism in education emphasizes the importance of spiritual and ethical values in the educational process. Nasr emphasized the need to instill transcendent values through the Sufi soul to overcome the secularization of knowledge and materialistic views in modern education